Flipped learning in malaysia - Abd Rahman, Siti Fatimah; Md Yunus, Melor; Hashim, Harwati (International Journal of Innovation, Creativity and Change, 2019)
The 21st century of education demands for student-centred learning rather than conventional teacher-centred learning. There are several new models and approaches to be adapted to meet the demand. One of the popular models in Malaysia is flipped learning. Flipped learning focuses on meaningful learning, and it also promotes a student-centred learning style. This paper explores flipped learning studies done by researchers regardless of the disciple and level of education.